1999
DOI: 10.1007/bf02351500
|View full text |Cite
|
Sign up to set email alerts
|

Project Neighborhoods in Action: An HIV-related intervention project targeting drug abusers in Washington, DC

Abstract: Project Neighborhoods in Action was a human immunodeficiency virus (HIV) outreach and intervention program that was conducted with injection drug users and crack users in several inner-city neighborhoods in the District of Columbia. Study participants were placed randomly in either a standard intervention or an enhanced intervention condition, with more than 800 persons being assigned to each group. Drug use frequency dropped from 15.2 days to 12.4 for alcohol (P <.0001), 2.1 days to 1.6 for marijuana (P < .00… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Research on the efficacy of educational sessions and interventions including these types of exercises has shown them to be effective at increasing proficiency and decreasing related HIV risk behaviors. 49,50 Related to this, a third way to alter people's attitudes toward condom use would be to target their overall sense of condom use self-efficacy. If people can be made to feel confident in their ability to use condoms correctly and confident in their ability to convince otherwise reluctant partners to use condoms, they will be less apt to feel that they want to avoid using condoms and more likely to engage in lowered-risk behaviors than their counterparts who lack such confidence in themselves and their abilities.…”
Section: Discussionmentioning
confidence: 98%
“…Research on the efficacy of educational sessions and interventions including these types of exercises has shown them to be effective at increasing proficiency and decreasing related HIV risk behaviors. 49,50 Related to this, a third way to alter people's attitudes toward condom use would be to target their overall sense of condom use self-efficacy. If people can be made to feel confident in their ability to use condoms correctly and confident in their ability to convince otherwise reluctant partners to use condoms, they will be less apt to feel that they want to avoid using condoms and more likely to engage in lowered-risk behaviors than their counterparts who lack such confidence in themselves and their abilities.…”
Section: Discussionmentioning
confidence: 98%
“…This inventory has been shown to have good concurrent and predictive validity and internal consistency [Hoffman, et al, 1999]. …”
Section: Methodsmentioning
confidence: 99%
“…These studies have found a number of social network characteristics to be associated with the individual’s drug use behavior. Characteristics identified have included having a high-frequency injector in one’s network [Trotter, Baldwin & Bowen, 1995], perceptions of needle sharing among peers [Neaigus, 1996], closed networks and networks with kinship ties [Latkin, 1995], larger network size and density of drug using network [Suh, et al, 1997; Schröder, 2001; Latkin, 1996], injecting at friends’ residences [Hoffman, 1999], having a current steady sexual relationship with a partner who is a PWID and high network turnover [Van Ameijden, 1994]. …”
Section: Introductionmentioning
confidence: 99%
“…They revealed on the one hand the expected interaction between the decrease in high-risk sexual behaviour and the decrease in drug use, and on the other hand the necessity to focus on the patterns of use prevailing in the respective target group and not on individual substances when implementing help programmes [19,28,29].…”
Section: Introductionmentioning
confidence: 99%